نماذج الزي المدرسي المفضلة لدى تلميذات المرحلة الابتدائية (Journal Of Educational and Psychological Researches, 2011)
A school uniform is an international educational phenomenon , and that eachstate through its pedagogical educational system imposes uniform hopping for goalsand visions that complement their theoretical framework, because of its extremeimportance that benefits the school administration, parents and pupils . The carriedout researches unanimous in various parts of the world on its importance,including : the achievement of equality between students and strengthen theiraffiliation to the school as well as the good appearance , and reduces competition inthe clothing and the maintenance of order in the classroom and school as well asincreases the seriousness and focus of students to study and make them known bothinside and outside the school and regulate their attendance for school withouthesitation. .It was therefore necessary to focus on school uniform ( its designs , fabrics andcolours ) so as to clothes in general and school uniforms special , privacy when girlsin the stage of late childhood, "because they are more interested in fashion" as wellas their tendency to favor the others desirability and specially their peers, and theirquest to confirm their esteem by their interest for clothing and express their opinionas naturally inclined and their ability to debate and dialogue about what preferably,their preferences affected by conditions, traditions of society, the environmentwhich they live in and the nature of their activities .The preferences of elementary school girls of samples of school uniforms mayhelp designers and officials in the ready-made clothes factories to manufacturecomfortable school uniforms to make them feel happy and have a right to expresstheir opinion and makes it easier for parents to provide uniform . For all of that, thecurrent research goal to identify the ( The designs and fabrics of school uniformpreferred by the elementary stage girls ). A sample of research which covers ( 1260 )females aged ( 9-12 ) years were chosen from the ranks of the fourth, fifth and sixthyear from (14) elementary school located in the center of the province of Baghdad ,(8) schools in the Rusafa and (6) schools in the Karkh district .The researcher was carried out the samples by herself accurately according tothe correct sewing foundations which include ( the preparation of the pattern ,cutting , marking , sewing, termination and ironing) in (5) samples dressed on fivesimilar dolls that can be carried .The most important findings of the research: -- The model number ( 2 ) (a shirt coloured in light heavenly and jumpercoloured in lowdark blue ) as the first choice , followed by the model number (4) ( a shirtcoloured inyellow and jumper oily colour ) , then the model number ( 3 ) (a shirt coloured inlightbeige and jumper coloured in brown ) , followed by the model number ( 5 ) (a shirtin light pink and jumper coloured in dark violet ) , and finally the modelnumber ( 1)(a shirt coloured in gray and jumper coluored in maronite ) .Finally, the researcher suggested some of her recommendations and proposals .